The MEMBANGUN MASA DEPAN PEREMPUAN SUMBA: PERAN PENDIDIKAN DALAM MENGATASI PERNIKAHAN DINI - Putra Wila (LPPM Universitas Negeri Surabaya, 2025)
Early marriage is still a significant social issue in Sumba, influenced by economic factors, culture and lack of access to education. This practice has a negative impact on women's health, education and economic independence. This research aims to analyze the role of education in preventing early marriage and increasing women's independence in Sumba. The method used is a literature review with a descriptive approach, referring to secondary sources such as government reports, statistical data, academic journals, and previous studies related to the issue of early marriage and education. The results show that education has a crucial role in raising awareness of women's rights, opening up economic opportunities, and changing social norms that support the practice of early marriage. Human Capital Theory, Feminist Theory, and Modernization Theory reinforce that education is an investment that can improve individual and community welfare. The conclusion of this study confirms that increasing access to education for women in Sumba is a strategic step in preventing early marriage and promoting women's emancipation. Therefore, policies that focus on educational equity and changing people's mindsets need to be strengthened to create a more supportive environment for the future of women in Sumba. Keywords: Women, Education, Early Marriage, Gender Equality, Future.